STUDI KELAYAKAN AIR TERJUN AWESALO SEBAGAI WISATA ALAM UNTUK MENDUKUNG KONSERVASI DI WILAYAH KPHL LAIWOI - Arniawati, Arniawati; Adami, Aryani; Manan, Abdul; Yordan, Muhammad Adam; Hartini, Hartini (Universitas Tanjungpura, 2023)
Awesalo Waterfall is one of the tourist destinations for the community, especially for the Konawe community, which is located in the KPHL Laiwoi area. The manager makes Awesalo Waterfall one of the objects that will be developed as a mainstay tourist destination. Nature tourism is a form of business development that is able to provide economic benefits for the community and area managers. The development of the Awesalo waterfall as a natural tourism object needs to pay attention to feasibility that does not conflict with conservation principles. This research is intended to examine whether or not Awesalo Waterfall can be developed as a natural tourism object. Data were collected through interviews, field observations, and related literature studies. The modified Guideline for Analysis of Operational Areas for Natural Tourism Objects and Attractions (ADOODTW) is used as a reference for analyzing the feasibility of Awesalo Waterfall. Based on the results of the study, the total feasibility value of Awesalo Waterfall can be developed as a natural tourism object reached 81.87%. These scores include attractiveness (87.5%), accessibility (75%), accommodation (75%) and amenities (90%). This value is included in the high category and can be developed to support sustainable management.Keywords: Awesalo waterfall , conservation, feasibility, KPHL Laiwoi, nature tourism